Gọi d là ƯC(n3+2n;n4+3n2+1)
n3+2n chia hết d;n4+3n2+1 chia hết d
n(n3+2n) chia hết d ; n4+3n2+1 chia hết d
n4+2n2 chia hết d; n4+3n2+1 chia hết d
(n4+3n2+1) - (n4+2n2) chia hết d
n2+1 chia hết d
n(n2+1) chia hết d
n3+n chia hết d
(n3+2n)-(n3+n) chia hết d
n chia hết d
n2 chia hết d
(n2+1)-(n2) chia hết cho d
1 chia hết d
d=1
PS tối giản
Gọi d là ước chung của \(n^3+2n\) và \(n^4+3n^2+1\) . ta có :
+) \(n^3+2n⋮d\)
\(\Rightarrow n\left(n^3+2n\right)⋮d\)
\(\Rightarrow n^4+2n^2⋮d\) (1)
Và \(n^4+3n^2+1-\left(n^4+2n^2\right)=n^2+1⋮d\)
\(\Rightarrow\left(n^2+1\right)^2=n^4+2n^2+1⋮d\) (2)
Từ (1) và (2)
\(\Rightarrow\left(n^4+2n^2+1\right)-\left(n^4+2n\right)^2⋮d\)
\(\Rightarrow1⋮d\Rightarrow d=\pm1\)
Vậy \(\frac{n^3+2n}{n^4+3n^2+1}\) là phân số tối giản (đpcm)